The Effect of Project-Based Learning Media on Students’ Critical Thinking Skills in Science Subjects for Grade IV at MI Miftahul Iman Poncowarno - Masri; Hanif Amrullah; Lutfi Fadilah (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to analyze the effect of project-based learning media on the critical thinking skills of fourth-grade students in science subjects at MI Miftahul Iman Poncowarno. This study uses a quantitative approach with a one-group pretest–posttest experimental design. The study population consisted of 30 students selected using a total sampling technique. Data were collected through pretest and posttest tests, observation, and documentation. Critical thinking skills were measured based on five indicators: identifying problems, analyzing cause-and-effect relationships, providing logical explanations, evaluating phenomena, and drawing conclusions. The results of the descriptive analysis showed an average pretest score of 48.50 and an average posttest score increased to 74.17. The N-Gain analysis showed an average of 0.49 with a moderate category. The paired t-test showed a significant difference between the pretest and posttest scores (t = -15.496, p < 0.05). The effect size value (Cohen's d) of 2.82 indicates a very strong influence of project-based learning media on students' critical thinking skills. Observations and documentation demonstrated active student involvement in designing and implementing experiments, discussing results, and drawing conclusions. These findings suggest that project-based learning media can enhance student engagement while supporting the development of critical thinking skills in elementary school science learning.